Dendrophyllia in Greek waters, Mediterranean Sea, with the first record of D. ramea (Cnidaria, Scleractinia) from the area - SALOMIDI, M.; ZIBROWIUS, H.; ISSARIS, Y.; MILIONIS, K. (Mediterranean Marine Science, 2010)
no abstract